2022
DOI: 10.1038/s41598-022-06862-9
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effect of Mulmina Mango against chemotherapy-induced cognitive decline in mouse model of mammary carcinoma

Abstract: The post-treatment status of breast cancer survivors has become a concern because of the toxicity induced by chemotherapeutic agents in the brain tissues resulting in cognitive deficits, which is generally referred as chemobrain. The aim of this study was to assess the effect of a proprietary ayurvedic formulation Mulmina Mango against chemotherapy-induced cognitive impairment (CICI). Mammary carcinoma was induced by subcutaneously inoculating 4T1 cells into the mammary fat pad of the animals. Intraperitoneal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Zinc sulfate prevented short term memory deficits in rats treated with the cytotoxic agent carmustine compared with controls 155. Interestingly, a study reported that mulmina mango ameliorated cognitive impairments and aided the maintenance of regular cytokine concentrations in rodents, with tumor size considerably reduced during cyclophosphamide, methotrexate, and 5-fluorouracil treatment 156. Phytochemical and antioxidant alkaloid piperlongumine prevented measurable social memory deficits in mice treated with a doxorubicin, cyclophosphamide, and docetaxel cancer regimen 157.…”
Section: Management Strategiesmentioning
confidence: 99%
“…Zinc sulfate prevented short term memory deficits in rats treated with the cytotoxic agent carmustine compared with controls 155. Interestingly, a study reported that mulmina mango ameliorated cognitive impairments and aided the maintenance of regular cytokine concentrations in rodents, with tumor size considerably reduced during cyclophosphamide, methotrexate, and 5-fluorouracil treatment 156. Phytochemical and antioxidant alkaloid piperlongumine prevented measurable social memory deficits in mice treated with a doxorubicin, cyclophosphamide, and docetaxel cancer regimen 157.…”
Section: Management Strategiesmentioning
confidence: 99%
“…Recently, John et al demonstrated the neuroprotective effect of lumina mango, Mangifera indica fruit pulp, Curcuma longa rhizome, Centella asiatica, and nutrient and vitamins [ 107 ]. Various studies suggested the neuroprotective, anti-inflammatory, and antioxidant properties of mangiferin [ 108 , 109 ].…”
Section: Possible Therapeutic Intervention For Chemotherapy-mediated ...mentioning
confidence: 99%
“…Various studies suggested the neuroprotective, anti-inflammatory, and antioxidant properties of mangiferin [ 108 , 109 ]. Mangiferin is a possible neuroprotective candidate against chemotherapy-induced neurotoxicity because of its ability to cross the blood-brain barrier [ 107 ]. In vivo studies revealed that combinatorial treatment of cyclophosphamide, Methotrexate, and 5-fluorouracil (CMF) reduced the burden of mammary cancer in mice and led to cognitive dysfunction.…”
Section: Possible Therapeutic Intervention For Chemotherapy-mediated ...mentioning
confidence: 99%
See 2 more Smart Citations